Use of Social Media by Academic Libraries in Australia: Review and a Case Study. Issue 1 (2nd January 2023) - Nguyen, Minh
ABSTRACT: This study examines social media use by academic libraries and consists of two parts. The first part surveys websites, and from the survey provides a picture of the current state of social media usage among university libraries in Australia. It also identifies Twitter, Facebook, Instagram, and YouTube as the most widely used social media platforms, and the University of Melbourne Library (UML) as the library which has attracted the most social media followers. In the second part of the paper, a content analysis is carried out on the UML's social media accounts. Findings demonstrate that the UML library uses Facebook more for sharing information and knowledge and showcasing facilities, places, and services; while the main purposes of Twitter are mainly for communicating and interacting, making news and announcements, and promoting library collections. 'Communication and interaction' is shown as the category of information most often posted on Twitter, the UML's main social media platform. It is also the one that attracts the highest level of engagement.